(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2021)
The complaint had been filed by the complainant namely Prabhat Kumar Singh bearing C.C. No. 3229(C) of 2016, pending before the Ld. Court of CJM, Patna dated 06.10.2016 is that his daughter has been virtually killed by the petitioner of the first case and the doctor sitting in the laboratory inasmuch as the petitioner of the first case has treated the daughter of the complainant negligently and the doctor sitting in the laboratory had failed to conduct further pathological test for dengue. The aforesaid batch of cases have been filed before Patna High Court against the order dated 24.12.2016 passed by the Ld. A.C.J.M., Patna in C.C. No. 3229(C) of 2016, whereby and whereunder cognizance has been taken against the aforesaid petitioners under Sections 304, 316/34 of the Indian Penal Code. In a case of alleged death due to criminal medical negligence, Patna High Court in its judgment dated: 14.08.2020 observed that for negligence to amount to a criminal negligence, the element of mens rea must be shown to exist and it is recklessness that constitutes mens rea in criminal law as far as negligence is concerned and there should be reckless state of mind and intention to cause harm and only then the same would amount to criminal negligence. Patna High Court concluded that it cannot be said that the petitioners have not followed the practice acceptable to the medical profession, which is apparent from the prescriptions and test reports annexed to the writ petitions. Division Bench of Supreme Court observed that it is clear that the Trial Court may have to call upon the complainant to first examine the professional Doctor as witness in support of the case made out in complaint and then proceed to consider the matter afresh on its own merits and in accordance with law. Trial Court shall proceed in the matter on its own merits without being influenced by any observation made in the two orders which have been set aside or for that matter in this order. All contentions and remedies available to both sides are left open.